GABPB1 activates transcription of ITPR3 and EMT in OSCC progression - Jun Liu; Chaoyue Zhao; Song Yang; Jichen Li (Functional & Integrative Genomics, 2026)

Over-expression of PtCRK2 gene enhanced resistance of Pinus tabuliformis against Bursaphelenchus xylophilus - Mengjia Yang; Yuxi Chen; Mengtian Li; Xin Zhou; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Improvement of near-infrared spectroscopic assessment methods for the quality of Keemun black tea: Utilizing transfer learning - Yurong Chen; Junhan Wang; Jingfei Shen; Yifan Zuo; Qianfeng Yang; Yongning Wei; Jichen Wang; Qing Yu; Wenjun Lv; Luqing Li (Food Research International, 2025)

MR2938 relieves DSS-induced colitis in mice through inhibiting NF-κB signaling and improving epithelial barrier - Ling Lv; Mireguli Maimaitiming; Shuli Xia; Jichen Yang; Tiantian Zhang; Yuming Wang; Xin Li; Iryna Pinchuk; Pingyuan Wang; Chang-Yun Wang; Zhiqing Liu (Marine Life Science & Technology, 2025)
Damage to the epithelial barrier is among key processes contributing to initiation and chronic inflammation in inflammatory bowel diseases (IBD). Only management therapy exists for IBD (e.g., anti-inflammatory and immunomodulatory agents, JAK/STAT inhibitors), and while novel therapeutic approaches have shown great potential, issues remain including route of administration, development of resistance to therapy and toxicity. Thus, novel small molecule inhibitors which can alleviate colonic inflammation and restore intestinal barrier functions are needed. Our previous study identified a new quinazolinone derivative MR2938, inspired by marine natural product penipanoid C, displaying impressive anti-inflammatory effects. In vivo efficacy study indicated that MR2938 had a dose-dependent effect on improving colitis symptoms, gut-barrier disruption, and colonic inflammation in an acute dextran sulfate sodium (DSS)-induced murine colitis as a model of epithelial injury relevant to IBD. Evaluation of potential mechanism involved in MR2938 efficacy demonstrated that MR2938 inhibited NF-κB-mediated inflammatory responses, and attenuated intestinal epithelial tight junction damage by restoring the expression of Occludin and ZO-1. Taken together, these data suggest that MR2938 is a promising lead compound for the treatment of IBD.

Ground response during of EPB shield shutdown in gravel ground based on coupled CEL-FEM analysis - Jinyang Fu; Jichen Xie; Hongyu Zhang; Haoyu Wang; Shuying Wang; Junsheng Yang (Computers and Geotechnics, 2025)

Distribution characteristics and ecological risk assessment of heavy metal pollution in seawater near the Yellow River Estuary of Laizhou Bay - Xiaojie Jin; Jichen Liu; Liming Wang; Xiaoxiao Yu; Jiaying Wang; Yang Jin; Shaonan Qiu; Jiaqi Liu; Yuting Zhao; Shan Sun (Marine Environmental Research, 2025)

Asymmetric linear conjugated polymers for stable H2O2 photosynthesis via internal polarization - Yunfan Yang; Yuming Dong; Wenwen Chi; Xinyu Sun; Jichen Su; Xinying Chen; Hui Zhao; Yongfa Zhu (Chemical Engineering Journal, 2025)

Microeukaryotic communities varied along the gradient in the seaweed habitats: A case study in a typical reef island in the East China Sea - Meiping Feng; Yijia Yang; Yunfan Zhang; Jichen Qiu; Wenhua Bian; Yifan Chen; Siting Hu; Kai Wang; Jian Zhang; Jun Lin; Shouyu Zhang (Regional Studies in Marine Science, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Prediction of SBRT response in liver cancer by combining original and delta cone-beam CT radiomics: a pilot study - Pengfei Yang; Jingjing Shan; Xin Ge; Qinxuan Zhou; Mingchao Ding; Tianye Niu; Jichen Du (Physical and Engineering Sciences in Medicine, 2024)

Characterization and functional analysis of the PtEXLA1 gene from poplar - Jiafu Liu; Yan Wang; Lihong Yang; Xue Wang; Junkang Zhang; Jichen Xu (Plant Biotechnology Reports, 2024)

Studies on the inhibition of α-glucosidase by biflavonoids and their interaction mechanisms - Huan Li; Jichen Yang; Mengfan Wang; Xiangzhao Ma; Xin Peng (Food Chemistry, 2023)

The expansin gene SmEXPA13 in Salix matsudana in association with plant salt tolerance - Junkang Zhang; Ruixia Yang; Yan Wang; Xue Wang; Lei Wang; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Citrobacter portucalensis Sb-2 contains a metalloid resistance determinant transmitted by Citrobacter phage Chris1 - Yanshuang Yu; Zhenchen Xie; Jigang Yang; Ruixiang Yang; Yuanping Li; Yongguan Zhu; Yanlin Zhao; Qiue Yang; Jichen Chen; Hend A. Alwathnani; Renwei Feng; Christopher Rensing; et al. (Journal of Hazardous Materials, 2023)

Over-expression of the Salix matsudana expansin gene SmEXPA23 enhances plant salt tolerance - Ruixia Yang; Lihong Yang; Xue Wang; Yan Wang; Junkang Zhang; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Laboratory study of Se speciation in the sediment and oligochaete Lumbriculus variegatus from an aquatic environment - Jichen Yang; Xin Yan; Hongsong Liu; Hongxing Chen; Wei Zhang; Wu Dong; Dan Li; Lingtian Xie (Environmental Science and Pollution Research, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Overexpression of the metallothionein gene PaMT3-1 from Phytolacca americana enhances plant tolerance to cadmium - Junkai Zhi; Xiao Liu; Peng Yin; Ruixia Yang; Jiafu Liu; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Transgenic creeping bentgrass plants expressing a Picea wilsonii dehydrin gene (PicW) demonstrate improved freezing tolerance - Hao Zhang; Yang Shi; Xinru Liu; Ruixue Wang; Jian Li; Jichen Xu (Molecular Biology Reports, 2018)

Response of microbial biomass and bacterial community composition to fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Changfa Liu; Jiao Liu; Zhiping Yang; Jin Li; Jichen Liu (Acta Oceanologica Sinica, 2017)

Grafting Resulted in a Distinct Proteomic Profile of Watermelon Root Exudates Relative to the Un-Grafted Watermelon and the Rootstock Plant - Yang Song; Ning Ling; Jinghua Ma; Jichen Wang; Chen Zhu; Waseem Raza; Yifei Shen; Qiwei Huang; Qirong Shen (Journal of Plant Growth Regulation, 2016)

Microbial communities of an arable soil treated for 8 years with organic and inorganic fertilizers - Chen Chen; Jianan Zhang; Min Lu; Chun Qin; Yahua Chen; Li Yang; Qiwei Huang; Jichen Wang; Zhenguo Shen; Qirong Shen (Biology and Fertility of Soils, 2016)

Study on the New Methods of Ship Object Detection Based on GNSS Reflection - Yong Lu; Dongkai Yang; Weiqiang Li; Jichen Ding; Ziwei Li (Marine Geodesy, 2013)

Identification and fine mapping of a mutant gene for palealess spikelet in rice - Qiong Luo; Kaida Zhou; Xianfeng Zhao; Qianchun Zeng; Hongai Xia; Wenxue Zhai; Jichen Xu; Xianjun Wu; Hongsong Yang; Lihuang Zhu (Planta, 2005)